2018
DOI: 10.1111/infa.12245
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Attuned Mind‐Mindedness, Infant Negative Affect, and Emotional Availability: Assessing Mind‐Mindedness during the Still‐Face Paradigm

Abstract: Mind‐mindedness captures caregiver orientation to infant mental states expressed in mind‐related comments to infant cues, typically assessed during free play. There are two orthogonal dimensions: Appropriate comments accurately interpret the infant's experience, and non‐attuned comments are judged by observers to be inaccurate interpretations. Appropriate comments have been consistently associated with optimal caregiving behavior, but less is known about non‐attuned comments, rare during free play. Further, av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Similarly, in a recent meta-analysis, nonattuned mind-mindedness predicted children’s insecure attachment more strongly than the absence of appropriate comments ( r = 0.45 versus r = 0.26; Zeegers et al 2017). Moreover, McMahon and Newey (2018) found that mothers’ use of nonattuned mind-related comments during a stressful situation (Still-Face Paradigm) was associated with dysregulated affect in their 6-month-old infants. Only when children are securely attached, they feel comfortable to explore their environment freely, engaging more easily in new social experiences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in a recent meta-analysis, nonattuned mind-mindedness predicted children’s insecure attachment more strongly than the absence of appropriate comments ( r = 0.45 versus r = 0.26; Zeegers et al 2017). Moreover, McMahon and Newey (2018) found that mothers’ use of nonattuned mind-related comments during a stressful situation (Still-Face Paradigm) was associated with dysregulated affect in their 6-month-old infants. Only when children are securely attached, they feel comfortable to explore their environment freely, engaging more easily in new social experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Insecure attachment may, therefore, be one of the mechanisms linking parental mind-mindedness to children’s behavior problems. Future research on the association between parents’ mind-mindedness and children’s difficulties should, therefore, include a measure of attachment, and should examine parents’ spontaneous use of mind-related comments in attachment-activating rather than free-play contexts, to increase the specificity and sensitivity of the measure (Bigelow et al 2015; McMahon and Bernier 2017; Milligan et al 2015; McMahon and Newey 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding age, associations were also obtained in EF, aligning with the proposal that there is significant development in this regulatory ability during the second year (e.g., Wiebe et al, 2010; Miller and Marcovitch, 2015). Although there were no age differences in ER performance, the absence of associations could be due to the fact that the responses to the SFP are fairly stable throughout the different ages, as the majority of studies have also found a lack of age effects (Mesman et al, 2009; McMahon and Newey, 2018). However, more research is needed using this paradigm at 2 years of age.…”
Section: Discussionmentioning
confidence: 88%